Size and development of tax evasion in 38 OECD countries: What do we (not) know? - Andreas Bühn; Friedrich Schneider (Center for Economic Studies and ifo Institute (CESifo), 2012)
For the first time we develop a time series of tax evasion (in % of official GDP) for 38 OECD countries over the period 1999 to 2010 based on MIMIC model estimations of the shadow economy. Considering indirect taxation and self-employment as the driving forces of tax evasion, we observe a declining trend of tax evasion between 1999 and 2010 for all countries. The average size of tax evasion across all 38 countries over the period 1999 to 2010 is 3.2% of official GDP. The country with the highest average value is Mexico with 6.8%, followed by Turkey with 6.7%; at the lower end we find the United States and Luxembourg with 0.5% and 1.3%, respectively.
Keywords: K42; H26; D78; O17; O50; H11; 330